AB0118 Supra-nuclear ophtalmoplegia in primary sjÖgren's syndrome. (1st June 2001) - Mugnier, B; Nicoli, F; Mattei, JP
Abstract : Background: Objectives: Neurological manifestations involving the central and the peripheral nervous systems (CNS, PNS) are observed in 10%-32% of patients with primary Sjögren's syndrome (pSS). If the lesions of the PNS have been perfectly described, data on CNS involvement in pSS, as for it, is controversial with regard in significance and aetiology. On occasion of an exceptional supra-nuclear ophtalmoplegia during pSS, we discuss relevance of CNS involvement in pSS. Methods: Results: A 61 year-old-woman encompassed several episodes of neurologic involvement resolving completely without any treatment: twice it consisted of mied nerves involvement (dysphagia) and dysaesthesia in the trigeminal territories and four times of supra-nuclear ophtalmoplegia with typical palsy of volontary lateral and vertical gaze compensated for oculo-cephalics reflexes. Repeated cerebral investigations excluded multiple sclerosis and vascular lesions. The absence of hypertonia, akinesia, or frontal syndrome associated to opthtalmoplegia, despite several years duration, reduces the probability of a Steele-Richardson disease. Neurologic signs onset began sixteen years before the diagnosis of pSS (grade III histologic lesions on minor salivary gland biopsy). Biochemical, immunologic and histological investigations did not reveal any other connective tissue disorders. This is the first case of supra-nuclear ophtalmoplegia developped in such a context. Oculo-motors troubles like nystagmus, ocular palsy, cerebellar syndrome and even internuclear ophtalmoplegia has been describe during pSS. Internuclear ophtalmoplegia is provoked by intra-axial lesions within the higher part of the cerebral trunk, above mesencephalic oculo-motor centres; however, a supra-nuclear lesion during pSS has never been reported so far. Through a literature review, we discuss relevance, aetiology and treatment of CNS involvement in pSS. Data are imprecise and even contradictory. Frequency of CNS involvement in pSS could vary from 0% to 25% and might display various patterns: focal or multi focal lesions entailing encephalon, cerebral trunk, cerebellum or medulla, but also more diffuse processes as an aseptic meningo-encephalitis or as a cognitive impairment. It's pathogenesis is poorly understood. Two mechanisms have been proposed: the first being of an ischaemic nature resulting from a vasculitis of small brain vessels, the second through an autoimmune response (humoral by anti-neuronal antibodies or cytotoxic). There is no clear consensus concerning the treatment of neurological complications of pSS. Corticosteroïds are usually initiated first; immuno-suppressive agents may be necessary in the absence of improvement. Conclusion: A supranuclear ophtalmoplegia can be observed in pSS; it reinforces the thesis of a CNS involvement in this connective disease, in so far such a characteristic symptom cannot be explained by a Steele-Richarson disease, a multiple sclerosis or vascular lesions. Be aware of CNS involvement in pSS would leed to realise a minor salivary gland biopsy that is the only exam useful to establish the diagnosis.